SISTEM INFORMASI E-COMMERCE PADA TOKO PERDANA JAYA BERBASIS WEBSITE - Karo karo, febrina Karo karo; Ridho, Muhammat Rasid (Computer Science and Industrial Engineering, 2021)
The quick advancement of data and correspondence innovation all throughout the planet opens up new freedoms for financemanagers with deals reach in all areas. Perdana Jaya Store Batam is an organization that partakes in the offer of electronic gear that offers different sorts and kinds of electronic merchandise, the interaction is completed at the Perdana store. Jaya Batam is as yet ordinary, clients go to the store to arrange electronic items. This specialist intends to make a Web based business application so clients or people in general can undoubtedly get to item data offered at the Perdana Jaya Batam store and can request and pay for electronic items on the web.The advancement of thisframework utilizes the PHP programming language and utilizations the Cascade model SDLC (programming improvement life cycle) and MySQL as the data set. The yield of this examination is an online showcasing data framework that makes it simple for clients to arrange items and saves clients'expenses and time